(untitled) (International Journal of Medical and Surgical Sciences, 2022)
Thyroid pathology is the morphofunctional evolution of the thyroid glands that leads to different types of clinical pictures. Within it is subclinical hypothyroidism, which is a biochemical alteration due to the elevation of thyroid-stimulating hormone (TSH) between 4.5 to 10 mUI that can occur with or without symptoms of multifactorial origin. The worldwide prevalence is 4-10% and Latin America 15-25%. 90% of patients with this pathology do not require treatment, but in turn there is an overmedicalization and underdiagnosis of it. This bibliographic review analyzes from its morphofunctional changes towards clinical criteria for a comprehensive approach to subclinical hypothyroidism, where we have an individualization by its comorbidities, age group, diagnostic algorithm, follow-up and differentiated treatment according to recent studies within this pathology. Therefore, an adequate diagnosis, follow-up and treatment provides a better lifestyle for patients.